The collections of the Anthropology division of La Plata Museum, Argentina - Del Papa, Mariano Carlos (Revista do Museu de Arqueologia e Etnologia, 2022)
The Anthropology Division of the Museum of Natural Sciences of La Plata, has under its institutional custody, one of the largest collections of human remains in South America. Its conformation represented the prevailing ideology in the ruling classes during the last decades of the 19th century and the beginning of the 20th century, and whose objective was to position it among the institutions of the civilized world. None of these actions could be understood outside the social and economic framework that prevailed in the Argentine Republic at that time. The need to expand the territories led to the implementation of expansionist policies on still unexplored territories, inhabited by native populations. In this way, the links between the colonizers and the original populations were transforming into manifestations with a greater degree of violence, finding in the Conquest of the Desert, the most complete expression of the prevailing socio-political situation. In this context, science played a preponderant role in several senses, since it not only gave legitimacy to military actions, but also made use of them with the aim of creating large naturalistic and anthropological collections. One hundred and twenty years later, the claims of the original communities, the actions of a state present before them and the interpellation of the scientific community began to reverse this situation through different mechanisms whose objectives are the establishment of reparatory policies for native communities.